2021
DOI: 10.1155/2021/5594505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Azadirachta indica and Senna siamea Decoction on CD4+ and CD8+ Level, Toxicological, and Antioxidant Profile in HIV/AIDS Positive Persons

Abstract: Acquired immune deficiency syndrome (AIDS) is a major public health problem affecting several countries with predominance in black Africa. Faced with therapeutic failure caused by resistance and supply disruptions, searching for other antiretroviral agents, in particular from natural sources, becomes necessary. Given popular consumption of Azadirachta indica and Senna siamea decoction in the Northern Cameroon region and the traditionally attributed antiretroviral value, information on its efficacy and safety c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…For instance, small trials have concluded that neem leaf extract given daily is safe and effective at improving CD4 + T cell counts in HIV patients ( Udeinya et al, 2004 ; Mbah et al, 2007 ). Furthermore, when A. indica and Senna siamea leaf extracts were given in combination with ART, this HIV patient group had improved T cell numbers and fewer markers of hepatic and renal toxicity than the group that was given ART alone ( Goni Hamad et al, 2021 ). To address the possibility of T cell exhaustion in HIV-infected patients, Olwenyi et al (2021) performed an in vitro study with peripheral blood cells isolated from infected and uninfected individuals; following exposure to enterotoxin, the lymphocytic response indicated that A. indica extract, but not the extracts from two other plants, was able to down-regulate CD4 + T cell activation in a concentration-dependent manner without affecting general T cell-specific functions.…”
Section: Antiviral Evidencementioning
confidence: 98%
“…For instance, small trials have concluded that neem leaf extract given daily is safe and effective at improving CD4 + T cell counts in HIV patients ( Udeinya et al, 2004 ; Mbah et al, 2007 ). Furthermore, when A. indica and Senna siamea leaf extracts were given in combination with ART, this HIV patient group had improved T cell numbers and fewer markers of hepatic and renal toxicity than the group that was given ART alone ( Goni Hamad et al, 2021 ). To address the possibility of T cell exhaustion in HIV-infected patients, Olwenyi et al (2021) performed an in vitro study with peripheral blood cells isolated from infected and uninfected individuals; following exposure to enterotoxin, the lymphocytic response indicated that A. indica extract, but not the extracts from two other plants, was able to down-regulate CD4 + T cell activation in a concentration-dependent manner without affecting general T cell-specific functions.…”
Section: Antiviral Evidencementioning
confidence: 98%
“…Many diseases including Alzheimer's disease, osteoporosis, acquired immune deficiency syndrome and atherosclerosis have been linked to GSH levels. [161][162][163][164] Therefore, detecting glutathione levels is an essential method for clinical processing and diagnosis of relevant diseases. However, current fluorescent probes are often subject to the external environment, which reduces their sensitivity and photostability due to photobleaching and premature leakage.…”
Section: Mno 2 For Fluorescence Imagingmentioning
confidence: 99%
“…Acquired immune deficiency syndrome (AIDS) is a malignant infectious disease caused by human immunodeficiency virus (HIV) invading CD4 + cells, resulting in imbalance and damage to human immune function, in turn causing serious harm to the human body [ 1 , 2 ]. HIV/AIDS has become a major global infectious disease and a serious global social problem affecting the world today [ 3 , 4 ]. In recent years, the speed of HIV transmission in some countries, the rate of AIDS-related deaths, and the incidence of AIDS have continued to increase worldwide [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%